The Role of Organizational Culture in Mediating the Relationship between National Cultures on Competitive Advantage - Kustyadji, Gatot (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the relationship patterns between national culture, organizational culture, and competitive advantage of the company that is conducted in 3 cement companies in Indonesia, namely in PT. Semen Gresik (Persero) Tbk., PT. Semen Padang, and PT. Semen Tonasa. The data is obtained by distributing questionnaires to managers in these three companies, and 180 respondents filled in the questionnaire completely. The analysis method is using quantitative descriptive analysis, while the statistical tool is using Structural Equation Modeling (SEM) with AMOS as the data processing technique. This study provides findings that support the previous researches, namely: 1) national culture has a positive significant influence on organizational culture; (2) national cultures has a positive significant influence on company competitive advantage; (3) organizational culture has a positive significant influence on company competitive advantage; (4) organizational culture mediates the relationship between national cultures towards company competitive advantage. Culture plays its role well in increasing company’s competitive advantage; becomes a differentiator between one organization and others; provide identity for each member of the organization; unite the organization; and shape the behavior of its members to behave appropriately, therefore with the existence of this culture, it can increase the company’s competitive advantage.